Quantifying neck muscle activity during head fixation in VR - Li, Guanlin; Weidner, Florian; Hu, Jinghui; Gellersen, Hans (Frontiers in Virtual Reality, 2025)
IntroductionHead-mounted displays (HMDs) are central to virtual and augmented reality (VR/AR) experiences, yet their reliance on head movement for interaction imposes physical demands on the neck. While neck pain is already a prevalent musculoskeletal issue, neck muscle activity during HMD usage remains poorly understood.MethodsIn this paper, we present the first empirical study of neck muscle activity during head fixation in a seated VR pointing task. Using surface electromyography, we measured muscle activity across 67 head poses in 15 participants.ResultsOur findings describe how neck muscle workload increases with rotation angle, is asymmetric across directions, and exhibits distinct temporal dynamics depending on head rotation angle. We contribute an open dataset and a detailed characterisation of neck muscle activity during prolonged head fixation, providing a physiological baseline for future research on the ergonomics of immersive technologies.DiscussionOur findings highlight how specific head orientations and fixation durations differentially load the neck musculature, offering the basis for a physiological explanation for discomfort during prolonged VR use and establishing a baseline for future ergonomic assessments.